TINDAKAN ABORSI YANG DILAKUKAN AKIBAT HUBUNGAN DI LUAR PERKAWINAN DITINJAU MENURUT UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Verliana Wulandari (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractThis study examines how the arrangement of abortion according to the Criminal Code (KUHP) and Law Number 36 Year 2009 on Health. This research is a scientific research to find the truth based on scientific logic from side of law by using legislation. Types of legal materials that the author uses are primary legal materials, secondary legal materials, as well as tertiary legal material. In the formulation of the Criminal Code (KUHP) does not give any room at all to the implementation of the act of abortion. The rules are set forth in articles 299, 346,347,348 and 349. Mean while, according to Law Number 36 Year 2009 on Health is regulated in Articles 75-77 and 194. Slightly different from the abortion arrangements in the Criminal Code, the abortion arrangements in the Health Act provide the space for the occurrence of abortion for some reason. Articles 75 the law provides two reasons for the abortion, which is a medical indication of a congenital / genetic defect or saves the lives of mother and rape victims that many affect the psychological victims. KEYWORDS  :  ACT OF ABORTION